1996
DOI: 10.1002/jez.1402740602
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of evolution inGraomys griseoflavus (Rodentia, Muridae). III. Olfactory discrimination as a premating isolation mechanism between cytotypes

Abstract: Graomys griseoflavus is a South American murid rodent showing a high degree of chromosomal polymorphism. We have recently demonstrated that cytotypes 2n = 36-38 form a complex reproductively isolated from the kariomorph 2n = 42, and that they may be considered separate species. Given the importance of olfactory perception for precopulatory recognition, we have investigated the ability of G. griseoflavus females to distinguish between odiferous stimuli from conspecific and heterospecific males by means of olfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…In the distribution area 2n=42–41 individuals inhabit the “Espinal” and “Western Chaco” phytogeographic regions located in central Argentina, while animals of complex 2n=38, 37, 36, 35 and 34 (2n=38–34) are found mainly at “Monte” region, in the western‐central area of the country. According to T heiler and B lanco (1996a) and T iranti (1998) there are no significant geographic barriers separating different populations of Graomys; in fact, these authors described narrow overlapping zones in some regions. Based on the cytogenetic and geographical distribution features, one could presume that Graomys agrees with the sympatric chromosomal speciation model proposed by W hite (1978).…”
Section: Robertsonian Fusions and Reproductive Consequencesmentioning
confidence: 64%
See 2 more Smart Citations
“…In the distribution area 2n=42–41 individuals inhabit the “Espinal” and “Western Chaco” phytogeographic regions located in central Argentina, while animals of complex 2n=38, 37, 36, 35 and 34 (2n=38–34) are found mainly at “Monte” region, in the western‐central area of the country. According to T heiler and B lanco (1996a) and T iranti (1998) there are no significant geographic barriers separating different populations of Graomys; in fact, these authors described narrow overlapping zones in some regions. Based on the cytogenetic and geographical distribution features, one could presume that Graomys agrees with the sympatric chromosomal speciation model proposed by W hite (1978).…”
Section: Robertsonian Fusions and Reproductive Consequencesmentioning
confidence: 64%
“…T heiler and B lanco (1996a, 1996b) also analysed the reproductive behavior of G. griseoflavus , finding interfertility among 2n=36, 37, and 38 karyotypes through laboratory mating tests. Those studies also showed the existence of reproductive isolation between 2n=36–38 complex and 2n=42 karyomorph: crosses between 2n=36–38 males and 2n=42 females were unreproductive, while crosses between 2n=42 males and 2n=36–38 females produced hybrid descendants.…”
Section: Robertsonian Fusions and Reproductive Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive isolation was clearly asymmetric; there was no copula between males 2n ¼ 36-38 and females 2n ¼ 42, whereas the reciprocal crossings (females 2n ¼ 36-38 Â males 2n ¼ 42) produced viable sterile hybrid offspring with 39 or 40 chromosomes (Theiler and Blanco 1996a). Theiler and Blanco (1996b) also found reinforcement of this post-zygotic isolation by mechanisms involving olfactory discrimination during female estrus. Females discriminated males of compatible chromosome complement from those that would produce non-viable offspring or sterile hybrids.…”
mentioning
confidence: 92%
“…Females discriminated males of compatible chromosome complement from those that would produce non-viable offspring or sterile hybrids. On the basis of these evidences, Theiler and Blanco (1996b) concluded that 2n ¼ 42 cytotype and 2n ¼ 36-38 complex are two sibling species.…”
mentioning
confidence: 96%